PENGARUH LIKUIDITAS, PROFITABILITAS, DAN LEVERAGE TERHADAP FINANCIAL DISTRESS (Studi empiris Pada Perusahaan Jasa Sub Sektor Transportasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2017) - siti masitoh (Universitas Muhammadiyah Tangerang, 2020)
This study aims to determine whether there is an effect of liquidity, profitability and leverage both simultaneously and partially on financial distress. The population in this study is a transportation sub-sector service company that has been listed on the Indonesia Stock Exchange in 2014-2017. With a total sample of 17 companies taken by purposive sampling. The research variable consisted of the dependent variable namely financial distress, independent variables namely liquidity, profitability and leverage. The research method used is descriptive statistical method. The analysis used is multiple linear regression analysis to find out the equation both simultaneously and partially towards the prediction of financial distress; correlation analysis to determine the relationship between liquidity, profitability and leverage both simultaneously and partially towards financial disress predictions; coefficient of determination to determine the contribution of the effect of liquidity, profitability and leverage both simultaneously and partially to financial distress predictions and t test hypothesis testing to determine the significance of liquidity, profitability and leverage both simultaneously and partially on financial distress predictions with the help of IBM SPSS Statistics 20The results showed that profitability and leverage had a significant effect on financial distress, while leverage did not significantly influence financial distressKeywords: liquidity, profitability, leverage and financial distress.